Transformation of cell physiology learning through collaborative integration of local wisdom of Mamanda arts - Dasim Budimansyah; Chairil Faif Pasani; Momod Abdul Somad; Kaspul Kaspul (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Conventional methods in learning cell physiology are less effective, so a more interactive approach is needed. Mamanda art offers an innovative solution by modeling biology concepts through drama, comedy, and dialogue, while instilling moral values and collaborative skills. The main objective of this research is to describe the learning activities of cell physiology through collaborative integration of local wisdom of Mamanda art. Collaborative character as a symbol of harmonious dynamics is applied in the learning process through Mamanda art media. This research is qualitative research with learning process observation method. The study population was two classes of participants in the Animal Physiology course, Biology Education Study Program, FKIP ULM. The sample used is a total sample. The first class amounted to 40 students; the second class amounted to 43 students. The two classes were compared qualitatively. The data were analyzed descriptively using a Likert scale of 1-5. The stages of learning are: First stage, introduction to the art of Mamanda and the concept of cell physiology; Second stage, division of labor and division of players; Third stage, Mamanda performance staging cell physiology models; Fourth stage, synchronization of cell physiology concepts and role playing in Mamanda art; and Fifth stage is case study. All stages of learning activities were observed by observers. The results showed that learning cell physiology through collaborative integration with local wisdom of Mamanda art can be implemented well. This learning model can also improve the character of collaboration by integrating the local wisdom of Mamanda art in students.Abstrak. Metode konvensional dalam pembelajaran fisiologi sel kurang efektif, sehingga diperlukan pendekatan lebih interaktif. Seni Mamanda menawarkan solusi inovatif dengan memodelkan konsep biologi melalui drama, komedi, dan dialog, sambil menanamkan nilai moral dan keterampilan kolaboratif. Tujuan utama penelitian ini adalah mendeskripsikan kegiatan pembelajaran fisiologi sel melalui integrasi kolaboratif kearifan lokal seni Mamanda. Karakter kolaboratif sebagai simbol dinamika yang harmonis diterapkan dalam proses pembelajaran melalui media seni Mamanda. Penelitian ini merupakan penelitian kualitatif dengan metode observasi proses pembelajaran. Populasi penelitian adalah dua kelas peserta mata kuliah Fisiologi Hewan, Program Studi Pendidikan Biologi, FKIP ULM. Sampel yang digunakan adalah sampel total. Kelas pertama berjumlah 40 mahasiswa, kelas kedua berjumlah 43 mahasiswa. Kedua kelas dibandingkan secara kualitatif. Data dianalisis secara deskriptif dengan menggunakan skala likert 1-5. Tahapan pembelajaran yaitu: Tahap pertama, pengenalan seni Mamanda dan konsep fisiologi sel; Tahap kedua, pembagian kerja dan pembagian pemain; Tahap ketiga, pertunjukan Mamanda yang mementaskan model fisiologi sel; Tahap keempat, sinkronisasi konsep fisiologi sel dan bermain peran dalam seni Mamanda; dan Tahap kelima, studi kasus. Semua tahap kegiatan pembelajaran diamati oleh pengamat. Hasil penelitian menunjukkan bahwa pembelajaran fisiologi sel melalui integrasi kolaboratif dengan kearifan lokal Kesenian Mamanda dapat terlaksana dengan baik. Model pembelajaran ini juga dapat meningkatkan karakter kolaborasi dengan mengintegrasikan kearifan lokal Kesenian Mamanda pada siswa.